2009
DOI: 10.1007/s11605-009-1046-9
|View full text |Cite
|
Sign up to set email alerts
|

A Matched Case-Control Study of Preoperative Biliary Drainage in Patients with Pancreatic Adenocarcinoma: Routine Drainage Is Not Justified

Abstract: In this case-matched control study, PBD was associated with a stent-related complication rate of 23% and resulted in a twofold increase in postpancreatectomy infectious complications. The routine use of PBD remains unjustified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 26 publications
4
73
0
3
Order By: Relevance
“…However, biliary decompression in those without symptomatic hyperbilirubinemia receiving upfront surgery may be avoided. [25][26][27] MRI/magnetic resonance cholangiopancreatography is considered to be equivalent to EUS/ERCP in the diagnostic setting.…”
Section: Imaging Evaluationsmentioning
confidence: 99%
“…However, biliary decompression in those without symptomatic hyperbilirubinemia receiving upfront surgery may be avoided. [25][26][27] MRI/magnetic resonance cholangiopancreatography is considered to be equivalent to EUS/ERCP in the diagnostic setting.…”
Section: Imaging Evaluationsmentioning
confidence: 99%
“…Recently, Van der Gaag et al reported results of a multi-center, randomized trial showing that endoscopic PBD did not have a beneficial effect on surgical outcomes for patients with pancreatic head cancer (18). Furthermore, it has been reported that among patients who underwent PBD, approximately 80% had a positive bile culture at the time of PD, resulting in infectious complications (19)(20)(21). They therefore did not recommend a routine PBD for patients who planned to undergo PD.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Although the results of the current randomized clinical study could not demonstrate any differences in bactobilia in perioperatively collected bile, it still offered arguments in favor of SEMS to optimize the preoperative course and the postoperative risk profile without the introduction of an enhanced risk for local complications. In previous studies it has been difficult to extract information about the true pros and cons of respective stent strategies, as only two studies, incorporating a limited number of patients, have compared plastic and metal stents for internal drainage [10,40]. However, a recent Dutch multicenter trial, with a case -control study design, demonstrated a clear superiority of SEMS [15].…”
Section: E804mentioning
confidence: 99%